PROSEDUR PENERJEMAHAN FRASA NOMINA RANAH SENI DALAM MAJALAH VOILÀ - Yusi Asnidar (Program Studi Sastra Indonesia, Fakultas Bahasa dan Seni, Universitas Negeri Jakarta, 2019)
This research is aimed at describing translation procedures using in noun phrases at Voilà Magazine. Translation procedures of Vinay and Dalbernet are categorized as direct translation (emprunt borrowings, calque, traduction littérale, literal translation, and indirect translation ( transposition, modulation, equivalence, and adaptation. Based on qualitative method, this research found that borrowings are more dominant in translation than calque and litteral translation. These procedures are used by translator to get semantic or formal equivalence. Transposition, modulation, equivalence, and adaptation are procedures used to get communicative or dynamic equivalence.